Violation of human rights as the basis for the threats to international security (Law and Safety, 2021)
Today our world faces an unprecedented convergence of transnational threats, armed conflicts, and instability spanning across the globe. Such human rights violations as mass killing, genocide, slavering, mass raping and others, together with other similar ones around the world, constitute a global threat to security. The main research question is identifying the nexus between human rights violations (concerning terrorism and migration) and threats to international stability on global levels. Therefore, the main goal of the research is to analyze these links and the role of different members of international relations (states) using global security challenges in their own interest while generating new waves of human rights violations and threats.
Keywords: human rights violation; global threats; security of the world and regions; international security; transnational threats; armed conflict.